2020
DOI: 10.1055/s-0040-1701608
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Glucocorticoids Reduce the Incidence of Refractory Hypotension in Low Birthweight Infants during the Early Neonatal Period, but Do Not Affect It beyond This Time

Abstract: Objective This study aimed to clarify the effect of antenatal glucocorticoids (AGs) on the incidence of refractory hypotension (RH) in very low birthweight (VLBW) infants after the first week of life. Study Design We included VLBW infants born at a gestational age of <30 weeks and divided them into three groups: the complete group (born within 7 days of completing a single course [two doses] of AGs), the incomplete group (born without complete course), and the late delivery group (born at ≥8 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
1
1
Order By: Relevance
“…Previous studies have shown that use of antenatal steroids is associated with higher systemic blood pressure and decreased vasopressor use in preterm infants. [18][19][20][21][22] However, we did not notice a significant relationship between lack of antenatal steroids use and likelihood of receiving vasopressors. This may be because the overall use of antenatal steroids was very high at baseline in our study population.…”
Section: Discussioncontrasting
confidence: 65%
“…Previous studies have shown that use of antenatal steroids is associated with higher systemic blood pressure and decreased vasopressor use in preterm infants. [18][19][20][21][22] However, we did not notice a significant relationship between lack of antenatal steroids use and likelihood of receiving vasopressors. This may be because the overall use of antenatal steroids was very high at baseline in our study population.…”
Section: Discussioncontrasting
confidence: 65%
“…Such a definition would prevent the overuse of inotropic drugs and unintentional aggregation of the severity of IVH [ 22 , 114 ]. Several studies indicate that hydrocortisone therapy is increasingly being used for refractory hypotensive preterm infants because such infants are proposed to have an inadequate hypothalamic-pituitary-adrenal axis response to stress during the first week of life [ 99 , 110 ].…”
Section: Postnatal Strategymentioning
confidence: 99%